الثقافة التنظيمية في الإدارة الجزائرية - العلجي, كنزة (مكتبة كلية الأدب العربي والفنون, 2023)
لكل إدارة ثقافة تميزها عن الأخرى وتجعل لها خصوصية في جميع نشاطاتها، إذ تعد الثقافة التنظيمية إحدى المحددات الرئيسية لنجاح الإدارة أو فشلها لكونها الوسط البيئي الذي تعيش فيه الإدارات، فالقيم والمعتقدات التي تستند عليها الإدارات في ترتيب أوضاعها الداخلية وعلاقاتها مع بيئتها الخارجية هي التي تحكم الأداء، وترسم الطريق نحو تحقيق الأهداف، ولقد بات ضروريا تبني الإدارة الثقافية لمفهوم الثقافة التنظيمية، فقد نشأ هذا المصطلح باعتباره عاملا منتجا لمناخ العمل، إذ تعد من المفاهيم المهمة في الإدارة الثقافية مما تتضمنه من قيم واتجاهات وأفكار توجه سلوك العامل في الإدارة التي يعمل بها وتؤثر في فعاليتها وكفاءتها الإنتاجية وذلك لما تؤديه الثقافة مندور مهم في تشكل قيمة العامل وطرق تعامله مع الأشخاص والأشياء التي حوله، فثقافة العامل هي التي تحدد نمط سلوكه وأساليب تفكيره وتصرفاته في المواقف المختلفة، ولما كانت الثقافة سلوكا يبتدعه العاملين وتتبناه الجماعات ويتشكل من اللغة والدين والعادات والتقاليد وبوسائل التي تندرج في المجال الثقافي والفني، وبما أن الموظفين لا يتركون قيمهم وأفكارهم خارج أبواب إدارتهم، فإن تلك المؤخرات الثقافية تؤدي دورا بارزا في التفاعل الاجتماعي داخل الإدارة الثقافية، لذا شهدت الثمانينات من القرن العشرين تطورا ملحوظا في الاهتمام بالثقافة التنظيمية على مستوى النظرية والتطبيق حيث كشفت دراسة أوت OTT أن ضعف الثقافة التنظيمية يجعلها غير فعالة في تحقيق أهدافها، ويؤثر سلبا على أنشطتها ويؤدي على هبوط مستواها. In the end, and based on what has already been discussed in the subject of our memorandum, which is tagged with: organizational culture in the Algerian administration, the Regional School of Fine Arts, ORAN, we concluded the following results: 1- The organizational culture is one of the most important elements of the administration’s success in facilitating its system and activities 2- Cultural activities in Algerian cultural institutions work to perpetuate the spirit of citizenship and the Algerian folk heritage 3- The cultural administration in Algeria contributes to the consolidation of the material and immaterial culture of the Algerian people 4- The cultural administration in Algeria embodies the spirit of the Algerian people and works to adopt and develop Algerian artists 5- The importance of organizational culture lies in the success of festivals and forums, which in turn devote themselves to the culture of the people and encourage preserving it. 6- The School of Fine Arts of ORAN is of great importance in developing the level of its students and a reservoir of Algerian talents in the field of fine arts. 7- The activities adopted by the school fall within the framework of the formation of the artist in the first place and the development of the recipient in the second degree, given that its activities are open to the recipients. 8- The organizational frameworks used in the school's activities are good, which made it achieve its goals 9- The school’s activities met with great success, which was embodied in the general impressions of it through what was published in newspapers, magazines and communication sites. 10- The regional school follows in its organizational frameworks the highest levels of professionalism and professionalism by following an arsenal of regulatory laws that guarantee the success of the management experience at its level.
مدرسة الجهوية للفنون الجميلة وهران أنموذجا
Keywords: الإدارة الثقافية،الثقافة التنظيمية